2015
DOI: 10.1016/j.amjmed.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacist Care for Hypertension in the Veterans Affairs Patient-centered Medical Home: A Retrospective Case-control Study

Abstract: Background and Purpose:We examined blood pressure 1 year after stroke discharge and its association with treatment intensification. Methods:We examined the systolic blood pressure (SBP) stratified by discharge SBP (<140; 141 to 160; or >160 mmHg) among a national cohort of Veterans discharged after acute ischemic stroke. Hypertension treatment opportunities were defined as outpatient SBP >160 mm Hg or repeated SBPs >140 mm Hg. Treatment intensification was defined as the proportion of treatment opportunities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…[9] Evidence from studies exploring the role of pharmacists in disease management highlight that pharmacist-led services can improve patients' self-management, treatment adherence, clinical outcomes [10,11] and appropriateness of prescribing. [16] There is a need to more fully utilise pharmacists' expertise and accessibility, working towards the provision of team-based approaches to patient care. [16] There is a need to more fully utilise pharmacists' expertise and accessibility, working towards the provision of team-based approaches to patient care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Evidence from studies exploring the role of pharmacists in disease management highlight that pharmacist-led services can improve patients' self-management, treatment adherence, clinical outcomes [10,11] and appropriateness of prescribing. [16] There is a need to more fully utilise pharmacists' expertise and accessibility, working towards the provision of team-based approaches to patient care. [16] There is a need to more fully utilise pharmacists' expertise and accessibility, working towards the provision of team-based approaches to patient care.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] However, few services are explicitly multifaceted, targeting both the patient's adherence and the clinician's prescribing. [16] There is a need to more fully utilise pharmacists' expertise and accessibility, working towards the provision of team-based approaches to patient care. [17] Therefore, the aim of this study was to explore patients' perspectives following a trial of a pharmacist-led multifaceted service in hypertension management.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that pharmacists are well suited to provide support, able to create effective relationships with providers and achieve high provider acceptance of pharmacist recommendations [24,25]. Furthermore, pharmacists have successful providers in patient-centered medical homes [26] and have provided care with demonstrated improved patient outcomes [27][28][29].…”
mentioning
confidence: 99%
“…For patients in the program, diastolic blood pressure decreased from baseline by À2.5 and À3.2 mmHg at 6 and 12 months, respectively, whereas controls had a diastolic blood pressure decrease from baseline by À1.1 and À1.2 mmHg at 6 and 12 months. Ultimately, patients who were referred to the pharmacist hypertension care management program had a significant improvement in blood pressure and indicated that this may be an effective method of improving blood pressure control among veterans in the patient-centered medical home model (Zillich et al, 2015).…”
Section: Future Models Of Primary Care For Texasmentioning
confidence: 99%